The Development of Drawdown Dolines and Subsidence Dolines with the Comparison of Their Bedrock Resistivities—A Case Study - Márton Veress (Hydrology)
The effect of the epikarst on the development of drawdown dolines and subsidence dolines is described. For this, the resistivity values of the bedrock determined by Vertical Electrical Sounding (VES) measurements were used. The higher resistivities below drawdown dolines are explained by the deeper position of the piezometric surface, while the low resistivity values below subsidence dolines can be traced back to the more elevated position of the piezometric surface. Resistivities increasing towards the centre of drawdown dolines refer to cavity heterogeneity increasing towards the centre and increasing vertical percolation rate, while decreasing resistivity values indicate an increasing degree of cavity fill above the piezometric level. At their asymmetrical variety, the bedrock of their opposite slope is of asymmetric resistivity, which is explained by the different elevations of the piezometric surface and the latter by different infiltration that took place on slopes with different inclinations. The same resistivity values of the doline with a flat floor indicate the homogeneous cavity formation of the epikarst. This latter results in homogeneous vertical infiltration, which favours horizontal dissolution. The piezometric surface is not deflecting below the subsidence dolines because resistivity differences are small between the bedrock below the doline and the bedrock of its environment. Below subsidence doline, above the piezometric surface, cavities develop (the resistivity is higher relative to the resistivity of the environment), and then the cavities become filled by suffosion (therefore, the resistivity below the doline is lower relative to its environment). The passage below the doline develops into a shaft as a result of its concentrated water supply and the epikarst is separated into parts.